Validity and Reliability of the Apple Watch for Measuring Heart Rate During Exercise - Khushhal, Alaa; Nichols, Simon; Evans, Will; Gleadall-Siddall, Damien O.; Page, Richard; O'Doherty, Alasdair F.; Carroll, Sean; Ingle, Lee; Abt, Grant (Sports Medicine International Open, 2017)
We examined the validity and reliability of the Apple Watch heart rate sensor during and in recovery from exercise. Twenty-one males completed treadmill exercise while wearing two Apple Watches (left and right wrists) and a Polar S810i monitor (criterion). Exercise involved 5-min bouts of walking, jogging, and running at speeds of 4 km.h−1, 7 km.h−1, and 10 km.h−1, followed by 11 min of rest between bouts. At all exercise intensities the mean bias was trivial. There were very good correlations with the criterion during walking (L: r=0.97; R: r=0.97), but good (L: r=0.93; R: r=0.92) and poor/good (L: r=0.81; R: r=0.86) correlations during jogging and running. Standardised typical error of the estimate was small, moderate, and moderate to large. There were good correlations following walking, but poor correlations following jogging and running. The percentage of heart rates recorded reduced with increasing intensity but increased over time. Intra-device standardised typical errors decreased with intensity. Inter-device standardised typical errors were small to moderate with very good to nearly perfect intraclass correlations. The Apple Watch heart rate sensor has very good validity during walking but validity decreases with increasing intensity.
Keywords: smartwatch; wearables; technology